THE IMPACT OF DIGITAL TRANSFORMATION ON EMPLOYEE ATTENDANCE MANAGEMENT IN UNIVERSITY - Achmad Sy Abdullah (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research aims to comprehend how technological changes and the role of transformational leadership affect employee discipline and operational efficiency in the context of university. The research methodology employs a qualitative approach with a focus on field research and case studies in several units within universities. Data were collected through direct observations and interviews with professors, administrative staff, and other employees involved in digital transformation. The findings indicate that the implementation of GPS-based digital solutions significantly impacts employee attendance management, enhances operational efficiency, and raises ethical challenges related to privacy. Transformational leadership proves to be a key factor in creating an environment that supports discipline and innovation. The conclusions drawn from this study provide a holistic overview of how digital transformation and transformational leadership can synergistically shape a new paradigm in employee attendance management in higher education.